Importing fascism: reappraising the British fascisti, 1923–1926. Issue 3 (2nd July 2016) - Stocker, Paul
Abstract: This article re-evaluates the ideology and significance of Britain's first self-proclaimed fascist party, the British Fascisti (BF) between 1923 and 1926. It challenges the dominant scholarly perception of BF ideology as a virulent form of conservatism or 'Conservatism with Knobs On' by demonstrating that they represent a hybrid movement consisting of both domestic conservative and continental fascist ideas. Thus, the chief purpose of this article is to demonstrate the dynamics of what scholars refer to as 'fascistisation' – the adoption and re-contextualisation of fascist features by non-fascist political movements and regimes. The BF's ideology represents an, at times, contradictory attempt to replicate the Italian Fascist movement and repackage it for a British audience – they were a 'fascistized' right-wing pressure group seeking a new, authoritarian state. Abstract notions of the 'success' of Mussolini's fascist experiment in stemming a Bolshevik revolution and his achievements in bringing order and a new sense of patriotism were re-adapted to the British context. These ideas were manacled to British conservative ideas of Christianity, anti-Socialism and imperialism typically associated with Edwardian Die Hards. Ultimately, the BF's ideology will be proved to be far more complex than scholars have been prepared to acknowledge during a period in which fascism was ill-defined.